"We Are Anxious Every Day": COVID-19 Impacts on Youth with Spina Bifida. (5th August 2021) - Stiles-Shields, Colleen; Kritikos, Tessa K; Ridosh, Monique M; Starnes, Meredith; Holmbeck, Grayson N
Abstract: Objective: This study examined the impact of the COVID-19 pandemic on a national sample of adolescents and young adults (AYA) with spina bifida (SB) and parents of youth with SB. Methods: AYA with SB (15–25; n = 298) and parents of children with SB ( n = 200) were recruited to complete an anonymous, online survey in English or Spanish. Participants provided information about demographic and condition characteristics, as well as their technology access and use for behavioral health care. They also completed the COVID-19 Exposure and Family Impact Survey (CEFIS), which includes Exposure, Impact, and Distress subscales. Exploratory correlations and t -tests were used to examine potential associations between CEFIS scores and demographic, medical, and access characteristics. Qualitative data from the CEFIS were analyzed using thematic analysis. Results: Scores on the Exposure, Impact, and Distress subscales demonstrated significant variability. Demographic associations with Exposure differed for those with higher Impact and Distress (e.g., White, non-Hispanic/Latino AYA reported higher rates of exposure [ p = .001]; AYA who identified with a minoritized racial/ethnic identity reported greater impact [ p ≤ .03]). Impacts to mental and behavioral health ( n = 44), interference with medical care ( n = 28), and interpersonal challenges ( n = 27) were the most commonly occurring qualitative themes. Conclusions: The current findings implicate differential impacts to individuals with SB and their families based on demographic, medical, and systemic factors (e.g., minoritized status). Recommendations to support families with SB and other pediatric conditions are made.